1993
DOI: 10.1177/136140969300700309
|View full text |Cite
|
Sign up to set email alerts
|

MS COSTAR: A Computerized Record for Use in Clinical Research in Multiple Sclerosis

Abstract: Mall, Vancouver, B.C., Canada V6T 2B5.MS COSTAR is an integrated computer software system, written in the MUMPS computer language, and is designed to facilitate both clinical care and clinical research in the setting of an MS clinic (1). It provides functions for storing, retrieving, analyzing, and displaying the demographic, clinical, and test data that accrue as patients are seen and cared for over time in a typical MS clinic. MS COSTAR is a specialized derivative of the COSTAR (COmputer STored Ambulatory Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
2
0
1
Order By: Relevance
“…This study and other childhood MS studies showed the female preponderance among EOMS (female/male ratio ϭ 2.87:1) when compared to adults. 22,26 In our study, the female preponderance was highest for subjects with disease onset at ages 13 (18 cases, female/male ratio ϭ 3.5:1) and 14 (26 cases, female/male ratio ϭ 7.67:1). Although numbers are small, these data support the theory that hormonal changes related to puberty, especially sex hormones, may play an important role in MS onset.…”
Section: Resultsmentioning
confidence: 43%
See 1 more Smart Citation
“…This study and other childhood MS studies showed the female preponderance among EOMS (female/male ratio ϭ 2.87:1) when compared to adults. 22,26 In our study, the female preponderance was highest for subjects with disease onset at ages 13 (18 cases, female/male ratio ϭ 3.5:1) and 14 (26 cases, female/male ratio ϭ 7.67:1). Although numbers are small, these data support the theory that hormonal changes related to puberty, especially sex hormones, may play an important role in MS onset.…”
Section: Resultsmentioning
confidence: 43%
“…Subjects were ascertained from the UBC MS Clinic's computerized database (MS-COSTAR). 22 Inclusion criteria for this study were 1) diagnosis of clinically definite (CD) MS 23 ; 2) clinical onset (first documented sign or symptom) before age 16; and 3) longitudinal follow-up at the UBC MS Clinic for at least 1 year. The studies based on MS-COSTAR are frequently reported as population-based.…”
mentioning
confidence: 99%
“…pacjentów, z czego ok. 4 tys. aktywnych[31,32]. D³ugoterminowe badania kontrolne by³y prowadzone przez ponad 20 lat przez g³ówn¹ klinikê uniwersytetu i dwa satelitarne ooerodki.…”
unclassified